Transparency and Policy Competition: Experimental Evidence from German Citizens and Politicians - Sebastian Blesse; Philipp Lergetporer; Justus Nover; Katharina Werner (Center for Economic Studies and ifo Institute (CESifo), 2023)
A lack of transparency about policy performance can pose a major obstacle to welfare-enhancing policy competition across jurisdictions. In parallel surveys with German citizens and state parliamentarians, we document that both groups misperceive the performance of their state's education system. Experimentally providing performance information polarizes citizens' political satisfaction between high- and low-performing states and increases their demand for greater transparency of states' educational performance. Parliamentarians' support for the transparency policy is opportunistic: Performance information increases (decreases) policy support in high-performing (low-performing) states. We conclude that increasing the public salience of educational performance information may incentivize politicians to implement welfare-enhancing reforms.
Keywords: H11; I28; D83; 330; yardstick competition; beliefs; information; citizens; politicians; survey experiment